1971
DOI: 10.1111/j.1432-1033.1971.tb01252.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA Polymerase, Triphosphates and Deoxyribonuclease in a Systemof Synchronized L Cells

Abstract: I n a system of synchronously dividing mouse fibroblasts (L cells), the activity of several enzymes was determined in relation to initiation of DNA synthesis. Synchrony of DNA synthesis and cell division was obtained by selective mechanical detachment of cells in mitosis, thereby avoiding the use of blocking agents. The activity of DNA polymerase under assay conditions permitting terminal or replicative activity to occur shows characteristic fluctuations throughout the life cycle of the cell: whereas the termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1972
1972
1982
1982

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Minor differences in activity behaviour under the assay conditions examined could be due to allotopic effects of one enzyme rather than indicative of the presence of different DNA polymerizing enzymes. It must be kept in mind, however, that a more or less substantial part of DNA polymerase activity is usually lost from the nuclei during isolation especially when an aqueous procedure is used (for further discussion of the "cytoplasmic" DNA polymerase activities see, e. g., a l so l22,2G,2S, 36,37,[39][40][41][42][43][44]. In this connection one might argue that high salt concentrations as used in this study can remove a membrane-attached DNA polymerase activity.…”
Section: Assays With Nuclear Sub Fractions and Microsomesmentioning
confidence: 99%
“…Minor differences in activity behaviour under the assay conditions examined could be due to allotopic effects of one enzyme rather than indicative of the presence of different DNA polymerizing enzymes. It must be kept in mind, however, that a more or less substantial part of DNA polymerase activity is usually lost from the nuclei during isolation especially when an aqueous procedure is used (for further discussion of the "cytoplasmic" DNA polymerase activities see, e. g., a l so l22,2G,2S, 36,37,[39][40][41][42][43][44]. In this connection one might argue that high salt concentrations as used in this study can remove a membrane-attached DNA polymerase activity.…”
Section: Assays With Nuclear Sub Fractions and Microsomesmentioning
confidence: 99%
“…Although this substantial evidence implies a direct correlation between activity of DNA polymerase I and the rate of replication of DNA in vivo, there is little evidence to support its direct association with the replication machinery of the cell nucleus. Earlier work with cell cultures synchronized with respect to the cell cycle by the use of metabolic inhibitors (Littlefield et al, 1963;Gold & Helleiner, 1964;Lindsay et al, 1970) or mitotic selection (Madreiter et al, 1971) revealed an increase in the total DNApolymerizing activity associated with the nucleus in S phase. However, this work was not definitive; in no case was the DNA-polymerizing activity identified.…”
mentioning
confidence: 98%
“…In the early days it seemed reasonable to expect that G , was a period necessary for the synthesis of enzymes and substrates directly involved in the subsequent DNA replication, but this has not proved the case for those studied so far. DNA polymerase activity, for example, often shows no clear relationship to the initiation of S-phase (Schindler, Grieder and Maurer, 1972); although in some cases increases in parallel with DNA synthesis have been seen they do not precede it (Friedman, 1970;Madreiter, Kaden and Mittermeyer, 1971;Slor, Bustan and Lev, 1973). The situation is actually complex, because mammalian cells contain at least three DNA polymerases, but even when this distinction is made no clear picture emerges (Spardi and Weissbach, 1974).…”
Section: A N Outline Of the Mammalian Cell Cyclementioning
confidence: 99%
“…It remains possible, however, that it starts even during S-phase. What is known is that chromosomes condense in response to some cytoplasmic factor, since unscheduled condensation can be induced by fusing mitotic cells with S-phase or G , cells (Johnson and Rao, 1970;Matsui et al, 1972). The type of condensation observed is not normal, however, and this suggests that the normal pattern depends upon some prior conformational preparations during S-phase.…”
Section: A N Outline Of the Mammalian Cell Cyclementioning
confidence: 99%